(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article examines the key threats to economic security in the healthcare system of the Russian Federation. The relevance of the study is substantiated, taking into account the importance of the sustainable functioning of healthcare for ensuring national security and social stability. The analysis of the main financial, organizational, managerial, social, technological and regulatory risks affecting the economic stability of the industry is carried out.